Chronic angle closure glaucoma: presentation and outcomes at a tertiary eye hospital of Saudi Arabia - Alzuhairy, Sultan A. (International Surgery Journal, 2018)
Background: Detection and management of chronic angle closure glaucoma (CACG) differ from primary open angle glaucoma (POAG). For general ophthalmologists in institutions with limited resources, timely detection and standard management of primary angle closure glaucoma (PACG) remains challenging. Methods: A retrospective chart review was performed of patients with CACG who presented to an eye unit in a hospital in central Saudi Arabia. Data were analyzed over a 5-year period regarding presentation, determinants and management outcomes of clinically diagnosed CACG cases. Results: The study sample was comprised of 102 eyes of 53 CACG patients. Bilateral disease at presentation was diagnosed in 92.4% patients. Nearly half of these patients were hypertensive, and more than one-fourth had diabetes or ocular comorbidities. Eighty eyes (78.4%) had a history of ocular surgery. A closed anterior chamber angle was detected in all eyes. The mean intraocular pressure (IOP) was 18.1±6.0mmHg, with or without medications. IOP greater than 22mmHg was detected in 26 (25.5%) eyes. The median cup-to-disk (CD) ratio was 0.6 [intraquartile range (IQR), 0.4; 0.7]. Laser peripheral iridotomy (PI) was performed in 61 eyes, trabeculectomy in 7 eyes, cataract extraction in 1 eye and combinations glaucoma surgeries in 7 eyes. Ninety-eight eyes had best-corrected visual acuity ≥20/200. The number of glaucoma medications declined significantly following surgery (χ2=32, P< 0.001). Conclusions: Laser PI was the main management modality for CACG in the study area. Goal of preventing blindness in eyes with CACG seems to be achieved.